Scoping review of social norms interventions to reduce violence and improve SRHR outcomes among adolescents and young people in sub-Saharan Africa - Luciana Leite; Rachel Yates; Gaia Chiti Strigelli; Jenny Yi-Chen Han; Jenny Chen-Charles; Jenny Chen-Charles; Maria Rotaru; Elona Toska; Elona Toska (Frontiers in Reproductive Health)
IntroductionDespite growing interest, guidance to inform effective social norms interventions that improve adolescents and young people's sexual and reproductive health and rights (SRHR) is needed.MethodsWe conducted a scoping review of experimental and quasi-experimental studies of social norms interventions in sub-Saharan Africa. Single and multi-component interventions that included a social norms component and assessed impacts on SRHR outcomes among 10- to 24-year-old adolescents and young people were included. We mapped interventions across eight programmatic strategies and six SRHR outcomes, drawing programmatic insights.ResultsN = 40 interventions from 12 countries reported effectiveness on intimate partner and non-partner sexual, physical and emotional violence (N = 14), child marriage (N = 6), sexual risk behaviours (N = 20), contraception and family planning (N = 23), prevention and treatment of HIV and other sexually transmitted infections (N = 17), and early pregnancy (N = 10). Intervention strategies included life skills approaches (N = 23), community dialogues (N = 14), school-based SRHR programming (N = 10), parenting programmes (N = 8), training of healthcare professionals on youth-friendly services (N = 7), media or digital-based approaches (N = 7), interventions with community leaders (N = 5), and rights-based advocacy (N = 2). Norms interventions can improve multiple SRHR outcomes, including reducing gender-based and intimate partner violence and child marriage, increasing HIV testing, and contraceptive use. Effective programmes were often implemented in combined interventions, and included life skills, community conversations, mass media and digital programmes with norms components.DiscussionIntegrating gender-transformative approaches such as reflections on gender roles and inequalities, youth sexuality, and gendered power relations, and engaging with reference groups were key to the success of programmes. Effective approaches delivered SRHR information alongside reflections on social norms, and combined participatory methods with a structured curriculum guiding activities led by trained facilitators. Most interventions focused on changing social expectations and awareness, but few reported clear diffusion strategies to ensure the spread of the new norms and behaviours for the expected change. Key evidence gaps identified include integrating implementation research to inform the scale-up and sustainability of effective social norms interventions. Social norms interventions that effectively address the needs of high-risk adolescents and young people are needed.